Preaching like Calvin: sermons from the 500th anniversary celebration - Hall, David W. (The Calvin 500 series, 2010)
Reformation, Calvinism, and lessons learned : Nehemiah 8:1-4a and 9:1-3, 16-21 / David W. Hall -- In Christ alone : Philippians 3:8-12 / Sinclair B. Ferguson -- Who is the wise and faithful servant? : Matthew 24:45-51 / Henry Luke Orombi -- In praise of predestination : Ephesians 1:3-6 / Bryan Chapell -- A great door for spreading the Gospel : 1 Corinthians 16:5-9 / Philip Graham Ryken -- All the glorious offices of Christ : 1 Corinthians 1:29-31 / Peter A. Lillback -- Calvin's cherished text : John 17:3 / W. Robert Godfrey -- John Calvin and guarding the Gospel : Galatians 1:6-10 / Steven J. Lawson -- Great intercessions : Romans 8:26-34 / Iain D. Campbell -- The Christian life : Philippians 2:12-13 / J. Ligon Duncan -- God's sovereign election : Ephesians 1:3-14 / Geoffrey Thomas -- Cherishing the church : Matthew 16:18b / Joel R. Beeke -- John Calvin and Psalm 110 : the Psalm for yesterday and today : Psalm 110 / Martin Holdt -- More than conquerors : Romans 8:35-39 / Edward Donnelly -- Of a thousand : Job 36:1-4 / Hywel Jones -- Bowing before the majesty of God : Romans 11:33-36 / Derek W. H. Thomas